Response of Slope Made Up of Soil and Other Waste Materials under Sinusoidal Motion - Nipa Chanda; Sima Ghosh; Manish Pal (Advances in Materials Science and Engineering)
Performance of small scale embankment slopes under dynamic loading is experimentally evaluated in the present work conducting shake table test. Model slopes are made up of soil and soil dust mixtures at various water level conditions. Material dust types as taken in the experiment are saw dust, stone dust, brick dust, and building demolish dust. Shear strength of soil such as cohesion and internal friction angle increases on an average 25% and 23%, respectively, when soil is mixed with 30% building demolish dust at different water content. Similarly other dust materials also enhance shear strength of soil. Responses of model slope on the basis of laboratory test have been observed and presented. At base frequency 5 Hz and 6% water content condition RMSA decreases up to 57% when slope material is changed from soil to “S + 30% DD” for slope with inclination 45° and at the same condition slope shows better stability which is reflected from reduction of base displacement as well as crest deformation up to 89% and 58%, respectively. Analytical solution of slope considering planer rupture surface is done using pseudodynamic method and results are compared with experimental observation. It is seen that when soil is mixed with 30% stone dust, sliding displacement of slope with inclination 45° is 7.5 mm at shake table test which is very closer to the analytical result. Stability of slope is maximum when “soil and building demolish dust” mixture is used and gradually reduces when slope material changes from “soil and brick dust,” “soil and stone dust,” “soil and saw dust” mixture, and ultimately soil. Thus, different material dust which we treat as waste can be used at various field conditions to enhance stability of embankment slope.